Hubungan Antara Umur, Tingkat Pendidikan, Masa Berkendara dan Pengetahuan dengan Perilaku Safety Riding (Studi pada Driver Ojek Online di Kelurahan Harapan Baru Kota Samarinda) - Steilla Switenia Puspita Alya Raintung; Emelia Tonapa; Yona Palin T (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
Internal factors are factors derived from humans in the form of innate human characteristics such as knowledge, gender, intelligence level, emotional level, motivation, and physical properties of a person while external factors are factors that exist in the surrounding environment such as the physical, social, cultural, economic and political environment. The results stated that 80%-85% of work accidents are caused by unsafe human behavior, so it is necessary to implement safety riding behavior so that accidents do not occur and can reduce the number of traffic accidents. The research is a analitik observational study with a cross sectional design. Sampling method that is using total sampling. The population in this study were all online motorcycle taxi drivers with a total of 39 people at the Harapan Baru sub-district post and the sample used 39 people. Data collection was carried out by researchers by interview method using a questionnaire, with univariate and bivariate analysis. Based on the results of the study, there is a relationship between age and safety riding behavior ρ value 0.009 (<0.05), there is no relationship between education level and safety riding behavior ρ value 0.093 (>0.05), there is a relationship between riding period and safety riding behavior ρ value 0.000 (<0.05) and there is no relationship between knowledge and safety riding behavior ρ value 0.443 (>0.05). In this study, variables related to safety riding behavior are age and riding period. It is expected to improve knowledge, attitudes and be able to practice safe safety riding behavior to avoid traffic accidents.